Revolutionizing sweetpotato breeding through heterosis exploiting breeding schemes - how far are we? - International Potato Center (2018)
Exploitation of hybrid vigor is one of the hallmarks of modern plant and animal breeding, but until recently had not been seriously considered by root and tuber breeders. In sweetpotato breeding, we have made exciting progress developing and implementing heterosis exploiting breeding schemes (HEBS) and are now applying this approach at breeding platforms across sub-Saharan Africa and in Peru (Fig. 1). We have completed a full cycle of reciprocal recurrent selection, the method used in heterosis breeding in Peru, and are now applying HEBS to speed up genetic gains in yield and important traits such as virus resistance, earliness, low-sweetness, as well as high iron and zinc.